(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Transport is an important element of the tourist infrastructure and constitutes the main integrated services included in the tourist product. The transport system of the Republic of Uzbekistan is under the jurisdiction of the Ministry of Transport. The Ministry is a public administration body for the development and implementation of a single state policy in the development of road, rail, air, river transport, subway, as well as road facilities.